The game plan of successful career sponsorship : harnessing the talent of aspiring managers and senior leaders - Ang, Jovina (Emerald Publishing Limited, 2019)
The career sponsorship relationship is a reciprocal and mutually beneficial relationship from which both the sponsor and sponsee can benefit. Jovina Ang presents new and comprehensive insights into career sponsorship, combining both the perspectives of the sponsee and sponsor to develop a model of career sponsorship and a framework for career success. She also explores how career sponsorship is different from mentorship and coaching, how the sponsorship relationship initiates and evolves over time, and the positive and negative outcomes that can arise from career sponsorship. This book provides theoretical and practical insights from across the world on the construct of career sponsorship. It lays out strategic game plans for how the aspiring manager, the senior leader and the wider organisation can leverage sponsorship, enabling individuals to achieve career success while contributing to organisational objectives. It also illustrates the broader implications of sponsorship as an investment in social relations and a form of modern social capital.- Resumé vydavatel
Keywords: rozvoj kariéry; profesní úspěch; career development; career success; elektronické knihy; monografie; electronic books; monographs